“There Aren’t any Dwarfs; They got out in Time”. Censored Image of the Home Army in Polish Poetry in 1956–1958 - Kloc, Agnieszka (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The paper focuses on censorship board’s approach to the subject of Home Army in Polish poetry from the period 1956−1958 of the liberalization of culture. The basic purpose of the research is focused on the identification of censorship reference to the image created by the authors. Moreover, it attempts to specify – on the basis of examples – the kind of content that was accepted, rejected or amended. Juxtaposition of the sensor’s reviews, “preventive inspection reports” and the content published works allows for the examination of the depth of the censor’s intervention and their methods of manipulating historical facts concerning the Hole Army. Research of the relationship censor-author allows for analyze “Aesop’s language” strategy. The whole of paper is based on a historical context and related phenomena, including the amnesty and so-called the “rehabilitation”.